FRONTLINE: 'Blood Money': A NZ investigative journalism case study - Karen Abplanalp (Asia Pacific Network, 2012)
Metro, the leading New Zealand glossy magazine reporting issues and society, published an investigative article ‘BLOOD MONEY’ probing the NZ Superannuation Fund (NZSF) investment in the controversial US-owned Freeport copper and gold mine at Grasberg as its lead feature in the December 2011 edition. Prior to this publication, the two Indonesian-ruled Melanesian provinces comprising West Papua on the island of New Guinea had remained largely ignored by New Zealand mainstream media for four decades. The mine has been at the centre of human rights and environmental abuse allegations for most of this period. In her investigation, the author sought to establish how the NZSF laid claim to being a ‘responsible investor’ while remaining involved in a mine with a long history of being implicated in alleged human rights violations and severe environmental damage. This exegesis considers the author’s reportage and methodology and how she included peace journalism concepts in the research and publication of ‘Blood Money’. It also analyses the public response.